The Study of Ma‘Ani Al-Hadis Towards Predictive Hadiths of Authoritarianism and the Moral Crisis - Sagirah, Sitti (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
Prophet Prediction is a tanabuāt which is related to his prophetic task for the events that have not yet occurred, but the occurrence can be sooner or later, and the event is certainly inseparable from the sociological conditions of the dinamical and developing society. To understand the hadith of the Prophet which is predictive, it needs to focus on various aspects, it starts from the semantic context and the linguistic structure of the hadith text, the appearance of the hadith, the position of the Prophet when delivering the hadith, the context of the mukhathab that followed the Prophet and how to connect the hadith text of the past to the present context. Therefore, it can capture meaning precisely, without forgetting its relevance to the contemporary dynamic context. The hadith of Sahih Muslim from Abu Hirairah which mentions two grups including the inhabitants of hell, predicts the occurrence of arbitrariness, injustice, and the moral crisis of political rulers who have impartial policies for the welfare of the people, and the existence of women who are increasingly brave to stimulate lust, and people who turn away from the big problems that are being faced.